Retrospective analysis of binocular vision anomalies (strabismus and non-strabismus) in a higher education optometry clinic, Kuantan, Malaysia from 2018 until 2021 - Ithnin, Mohd. Hafidz; Othman, Shah Farez; Ramli, Cik Nurul Aina Izatie (IIUM Press, 2023)
Introduction: Binocular single vision is required to see a single image with both eyes, so any disorders will impair visual function. It is supported by the normal visual apparatus, as well as sensory and motor systems. The anomaly on each component might lead to non-strabismus which are accommodation and vergence, as well as strabismus anomalies. Aim: This study was aimed to evaluate the retrospective data of non-strabismic and strabismic cases at International Islamic University Malaysia (IIUM) Optometry Clinic, Kuantan, Malaysia from 2018 until 2021. Methodology: A clinically based retrospective study was conducted, and all patients’ files were thoroughly reviewed, and data collected were analyzed by different categories. The categories included demographic information such as age, gender, occupation, location, non-strabismus anomalies, including accommodation and vergence anomalies, as well as the type of strabismus. Results: The total sample size for the study was 91, with female participants accounting for 51.6 % of the total. The patients' ages ranged from 3 to 35 years (mean age: 12.03 ± 6.64 years), with one-third of them being under the age of ten. Most patients came from Pahang, with 57.1 % from the Kuantan district. 82 of the patients were still students, and the remaining of them worked as officers or non-officers. The most common cases were accommodation insufficiency, which affected 19.8 % of patients, while basic exophoria affected 9.9 %. Out of all strabismic patients, 67 patients had alternating exotropia at distance and near. Conclusion: Accommodation insufficiency, basic exophoria and intermittent exotropia dominated the binocular vision anomalies cases at the clinic. This data could be used in the clinic to forecast the trend of cases for the coming year. The awareness and prevention should be taken to reduce the number of cases especially on children.